Migrations and culture. Essential reflections on wandering human beings - Contini, Paolo; Carrera, Letizia (Frontiers in Sociology, 2022)
It is possible that our century and the one just past will be remembered in the future as the centuries of migration. Faced with the extent of migrations of our day, social scientist ask themselves several questions, and in particular they examine the causes of migration, the integration of immigrants in the host countries and the elaboration of their cultural identity. The newcomers are almost always poorer than those who had already settled before, with different language, physical appearance, customs, beliefs and religious practices. The widespread perception is that of an upheaval of the social order. For some, it is the dawn of a new world, under the banner of métissage (or hybridisation) and universal brotherhood; for most, it is the beginning of an invasion. Immigration is always a matter of borders: who is “us”? Who is “them”? The host society has the power to define, classify and build the social category of immigrants. In this scenario, urban spaces represent the stages on which the encounter with difference is staged. The space is never neutral and is actually able to affect, even heavily, the conditions of that encounter. The physical form of the city is the result of widespread social representations of all phenomena, but it is also able to act on the same social representations by altering the processes that take shape in it. The urban dimension and the redesign of the urban space become the more and more one of the strategic keys to shape and govern social processes aimed at governing the transformation processes in a multi-ethnic sense of the European societies. Urban govern policies, consequently, can either wait for spontaneous processes of integration and virtuous composition of differences, or implement actions to “govern” differences, to prevent potential conflicts and start processes of active inclusion. In order to support the act of wandering within this second pattern of urban policies, moving from simple tolerance to a Habermasian process of dialogical confrontation, at least two conditions are necessary: the presence of public common spaces, the quality of policies for regulating the use of urban public spaces.